Returning to ceremony : spirituality in Manitoba Métis communities - Fiola, Chantal, 1982- (University of Manitoba Press, 2021)
"Returning to Ceremony is the follow-up to Chantal Fiola's award-winning Rekindling the Sacred Fire and continues her ground-breaking examination of Métis spirituality, debunking stereotypes such as "all Métis people are Catholic," and "Métis people do not go to ceremonies." Fiola finds that, among the Métis, spirituality exists on a continuum of Indigenous and Christian traditions, and that Métis spirituality includes ceremonies. For some Métis, it is a historical continuation of the relationships their ancestral communities have had with ceremonies since time immemorial, and for others, it is a homecoming - a return to ceremony after some time away. Fiola employs a Métis-specific and community-centred methodology to gather evidence from archives, priests' correspondence, oral history, storytelling, and literature. With assistance from six Métis community researchers, Fiola listened to stories and experiences shared by thirty-two Métis from six Manitoba Métis communities that are at the heart of this book. They offer insight into their families' relationships with land, community, culture, and religion, including factors that inhibit or nurture connection to ceremonies such as sweat lodge, Sundance, and the Midewiwin. Valuable profiles emerge for six historic Red River Métis communities (Duck Bay, Camperville, St Laurent, St François-Xavier, Ste Anne, and Lorette), providing a clearer understanding of identity, culture, and spirituality that uphold Métis Nation sovereignty."--